Barriers to entrepreneurial development in technical and vocational education and training (TVET) colleges: A cross-sectional mixed-methods study of student perspectives. - Mbanjwa, Sibonelo Thanda (Student’s Journal of Health Research Africa, 2025)
Background Entrepreneurship is increasingly recognized as a pathway to youth empowerment and economic development in South Africa. Technical and Vocational Education and Training (TVET) colleges play a pivotal role in equipping students with practical skills for self-employment. However, despite national policy support, entrepreneurial development within TVET colleges remains constrained. This study investigates the barriers hindering entrepreneurial growth from the perspective of enrolled students, with a focus on identifying institutional, structural, and contextual challenges. Methods A cross-sectional mixed-methods study was conducted across four public TVET colleges in KwaZulu-Natal. Quantitative data were collected through structured questionnaires administered to 120 final-year students enrolled in business and engineering programs. Qualitative insights were gathered through focus group discussions (n = 4) and semi-structured interviews with 12 student representatives and academic staff. Descriptive and inferential statistics were used to analyse quantitative data, while thematic analysis was applied to qualitative responses. Results Key barriers identified include inadequate entrepreneurial training (reported by 72% of students), limited access to start-up funding (68%), lack of mentorship and incubation programs (61%), and insufficient exposure to real-world business environments. Institutional constraints such as outdated curricula and poorly resourced entrepreneurship units further compound the challenge. Qualitative findings highlighted students’ strong preference for experiential learning approaches, including internships, community-based enterprise projects, and simulation exercises, which they perceived as essential for bridging the gap between theory and practice. Conclusion The study highlights significant structural and pedagogical gaps within TVET institutions that hinder students’ entrepreneurial readiness. While students demonstrate interest and potential for entrepreneurship, systemic limitations restrict the translation of skills into practice. Recommendations To strengthen entrepreneurial development in TVET colleges, curriculum reforms should prioritize experiential learning, partnerships with local businesses, and on-campus incubation centres. Additionally, policy frameworks must support funding access and mentorship networks tailored to student-led enterprises.